Outsourcing and political power: bureaucrats, consultants, vendors and public information technology. - Peled DA (Public Personnel Management)
The rapidly growing governmental IT outsourcing trend raises different questions: Who, inside bureaucracy, governs computer systems after outsourcing? Which actors gain or lose political clout when the government begins to aggressively outsource i ts IT operations? How does IT outsourcing change the relationships among bureaucrats, consultants, and vendors? The article highlights the increasingly important and behind-the-scenes role the consultant plays as an intermediary between the MIS bureaucra t and technological vendors. IT consultants exert an enormous amount of political power because they are the 'glue' binding together all the actors involved in producing and maintaining public information technology. Regrettably, this new consultant-cent ered environment is responsible for the degradation of the organizational and technological skills of MIS bureaucrats and also impairs the feedback information flow between bureaucrats and vendors regarding the status of public computer projects. Theref ore, the article suggests that the unchecked power of IT consultants hinders the ability of bureaucrats to be accountable for the systems they manage.